The relationship between training load and pain, injury and illness in competitive swimming: A systematic review. (March 2021) - Barry, Lorna; Lyons, Mark; McCreesh, Karen; Powell, Cormac; Comyns, Tom
Abstract: Background: Research suggests that the frequency of training, combined with the repetitive motion involved in high volume swimming can predispose swimmers to symptoms of over-training. The prevention of pain, injury and illness is of paramount importance in competitive swimming in order to maximise a swimmer's ability to train and perform consistently. A significant factor in the prevention of pain, injury or illness is the appropriate load monitoring and management practices within a training programme. Objective: The purpose of this systematic review is to investigate the relationship between training load and pain, injury and illness in competitive swimmers. Methods: The databases SPORTDiscus, CINAHL, Scopus, MEDLINE and Embase were searched in accordance with PRISMA guidelines. Studies were included if they reported on competitive swimmers and analysed the link between training load and either pain, injury or illness. The methodological quality and study bias were assessed using the Joanna Briggs Institute Critical Appraisal Checklist. Results: The search retrieved 1, 959 articles, 15 of which were included for review. The critical appraisal process indicated study quality was poor overall. Pain was the most explored condition (N = 12), with injury (N = 2) and illness (N = 1) making up the remaining articles. There was no evidence of an association between training load and pain, while there may be some evidence to suggest a relationship between training load and injury or illness. Conclusions: The relationship between training load and pain, injury or illness is unclear owing to a host of methodological constraints. The review highlighted that youth, masters and competitive swimmers of a lower ability (e.g. club versus international) may need particular consideration when planning training loads. Winter periods, higher intensity sessions and speed elements may also need to be programmed with care. Monitoring practices need to be developed in conjunction with consensus guidelines, with the inclusion of internal training loads being a priority. Future research should focus on longitudinal prospective studies, utilising the session Rating of Perceived Exertion (sRPE) monitoring method and investigating the applicability of Acute/Chronic Workload Ratio (ACWR) and exponentially weighted moving average (EWMA). Improved methods and study design will provide further clarity on the relationship between load and pain, injury, and illness. Highlights: Internal training load monitoring should be included in competitive swimming environments consistent with IOC guidelines. Pain, injury and illness definitions need to be standardised in accordance with FINA guidelines. Methodological variations prevent accurate comparison of results and hamper the synthesis of the findings. Longitudinal prospective studies, including sRPE with an emphasis on pain, injury and illness incidence are recommended.